THE INFLUENCE OF DEPRECIATION ACCOUNTING ON NATIONAL INCOME. - Hendriksen, Eldon S. (The Accounting Review, 1951)
Abstract The accounting for depreciation is important to the economist as well as to the accountant because of the possible effects of miscalculated depredation rates on national income and employment. Since it is necessary to use accounting data or statistics derived from accounting data in the study of the relationships of depreciation to national income and gross national product, it is important that there be complete understanding of the accounting and economic uses of the term "depreciation." Current accounting methods produce depreciation rates which are quite rigid over time because they are based on the cost of depreciable assets and the most widely used methods allocate these costs uniformly over time rather than according to use. It is quite often assumed that this rigidity produces excessive depreciation rates during periods of low activity and inadequate depreciation rates during periods of expanding or high activity. It is probable that these depreciation rates are excessive or inadequate in an economic sense more than in an accounting sense. This excess or inadequacy becomes important to national welfare if it has an unfavorable effect on the general level of business activity. An investigation of the consequences of excessive or inadequate depreciation rates must involve an investigation of direct or indirect effects on consumption and investment. It is claimed that during periods of low activity, excessive depreciation rates prevent the payment of dividends and thus curtail consumption. This would be true if it can be assumed that by decreasing depreciation rates, dividends would be increased. This does not seem likely since many corporations report no profit or a loss during depression periods. Furthermore, it is probable that dividends would not be increased during such periods because of a desire to increase safety margins and because of tighter credit markets and falling income. Rather, there is a tendency to maintain dividends because of a desire to enforce a rigid dividend policy irrespective of the business cycle. It is more probable that depreciation rates may have an effect on investment through profit expectations. That is, excessive depreciation rates during a period of contraction might cause greater pessimism as to profit expectations and inadequate depreciation rates during periods of expansion might lead to over-optimism. Thus, it would cause less investment when it is needed most and too much investment when inflation is already in process. This however, is not conclusive nor does it appear to be of a very large magnitude. This does seem to provide some argument in favor of depreciation methods which would provide for greater charges during high activity and smaller charges during low activity. The most practical method would seem to be that which bases the amount of depreciation or a part of it (the "user cost") on the amount of production. Proposed methods which would base the depreciation charge on replacement cost or purchasing power indexes would also further increase the economic significance of accounting depreciation.